Perbandingan Sistem Pendidikan Amerika Serikat dengan Indonesia - Zikri Gusnita; Mislaini Mislaini; Nidaul Lathifah Suhelmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Education is a place where initially people who don't know anything can find out and education is very important for all human beings, both in Indonesia and other countries. Basic education is an important part of the education system. Through basic education, students are provided with scientific concepts, moral cultivation, character formation and other basic knowledge needed in social life. The aim of writing this article is to examine the comparison of Indonesia's basic education system with that of the United States. The research approach used is a literature study by reviewing several previous research studies and by analyzing learning videos in each country that are viewed on YouTube. Data analysis uses qualitative descriptive methods. The results obtained are that there are differences in basic education policies in Indonesia and the United States. These differences can be seen from the curriculum system and structure used. However, both Indonesia and the United States have tried to implement the best basic education system according to the capabilities of their respective countries. Keywords: Education system, United States, Indonesia